Proteomic Analysis Reveals Proteins Involved in Seed Imbibition under Salt Stress in Rice - Xu, Enshun; Chen, Mingming; He, Hui; Zhan, Chengfang; Cheng, Yanhao; Zhang, Hongsheng; Wang, Zhoufei (Frontiers in Plant Science, 2017)
Enhancement of salinity tolerance during seed germination is very important for direct seeding in rice. In this study, the salt-tolerant japonica landrace Jiucaiqing was used to determine the regulators that are involved in seed imbibition under salt stress. Briefly, the comparative proteomic analysis was conducted between dry (0 h) and imbibed (24 h) seeds with 150 mM NaCl. Under salt stress, the uptake of water increased rapidly before 24 h imbibition (Phase I), followed by a plateau of seed imbibition from 24 h until 96 h imbibition (Phase II). We identified fourteen proteins involved in seed imbibition, in which the majority of these proteins were involved in energy supply and storage protein. The early imbibition process was mediated by protein catabolism; the most of proteins were down-regulated after 24 h imbibition. Eleven genes were earlier expression during seed imbibition (12 h and 24 h) under salt stress compared to water condition. By comparison, 2,3-bisphosphoglycerate-independent phosphoglycerate mutase (BPM), glutelin (GLU2.2 and GLU2.3), glucose-1-phosphate adenylyltransferase large subunit (GAS8), and cupin domain containing protein (CDP3.1 and CDP3.2) were near the regions of quantitative trait loci (QTLs) for seed dormancy, seed reserve utilization, and seed germination in Jiucaiqing. In particular, CDP3.1 was co-located in the region of qIR-3 for imbibition rate and qGP-3 for germination percentage. The role of CDP3.1 was verified in enhancing seed germination under salt stress using T-DNA mutant. The identified proteins might be applicable for the improvement of seed germination under salt stress in rice.